Conductor-insulator quantum phase transitions - Dobrosavljevic, Vladimir; Trivedi, Nandini; Valles, James M. (Oxford : Oxford University Press, 2012)
"Quantum phase transitions describe the violent rearrangement of electrons or atoms as they evolve from well defined excitations in one phase to a completely different set of excitations in another. The chapters in this book give insights into how a coherent metallic or superconducting state can be driven into an incoherent insulating state by increasing disorder, magnetic field, carrier concentration and inter-electron interactions. The problem necessarily involves many interacting particles and therein lies the challenge to develop a multi-faceted theory. Experiments probing microscopic structure, transport, charge and spin dynamics provide important clues. What sets this book apart is a strong dialog between experiment and theory that has the potential to solve some major issues in many-body physics. The ideas and methods developed here are bound to have repercussions in all spheres of physics."--P. [4] of cover.
Includes bibliographical references.
Keywords: Phase transformations (Statistical physics).; Quantum statistics